An Investigation of Affective Reactions to the First-Time Administration of an English Oral Elicited Imitation Test and Oral Narrative Test - Bielak, Jakub; Mystkowska-Wiertelak, Anna; Pawlak, Mirosław (Studia Anglica Posnaniensia, 2020)
As some language tests may be more anxiety-provoking than others, anxiety, other affective reactions, and related perceptions evoked by the English oral elicited imitation test (EI), a sentence repetition task measuring the implicit knowledge of grammar in a way not resembling natural communication, were investigated during first-time administration by means of a 10-point rating scale and a thought-listing tool. Because anxiety and other emotions cannot be interpreted in absolute terms, the same reactions induced by a special type of an English oral narrative test (ON) were investigated for comparison. A quantitative and qualitative analysis revealed EI to be more anxiety-provoking than ON as it created considerably higher levels of tension and worry. The possible causes include the perception of EI as very difficult, the uncertainty and confusion generated by the oral nature of its instruction and stimuli, and lack of an openly declared focus. Careful administration of EI is recommended to reduce anxiety and unfavorable perceptions. Other, much less frequent affective reactions to the tests and perceptions included satisfaction, curiosity, excitement, hope, confusion, interest, boredom, uncertainty, and concentration.